Rohingya Ethnic Conflict in Myanmar 2017 to 2023 Reviewed from International Humanitarian Law and Human Rights - Firmansyah, Maman Dicky; Tarmanto, Untung; Halilintar, Edo Sidharta (AGUSPATI Research Institute, 2024)
The Rohingya ethnic group is one of the minority ethnic groups living in Myanmar. This ethnic group is suspected of receiving less attention from the state and is even being marginalized. Discrimination against the Rohingya ethnic group is due to the weak role of the state in providing protection. This discrimination is also accompanied by open violence, supported by the majority of the fanatic masses of the military junta government. The Rohingya ethnic group has become the